Isolation and biochemical characterization of the iC3b receptor of Candida albicans. - Alaei, S (1993)
In an effort to identify the protein structure on Candida albicans, pseudohyphal forms which had been shown earlier to bind human iC3b, a protein of about 42 kDa (p42), were obtained from lysates of pseudohyphal forms by absorption with C3(H2O)-Sepharose. An antiserum raised in rabbits against this protein effectively inhibited adherence of sheep erythrocytes carrying iC3b (EAC3bi) to pseudohyphal forms. p42 cross-reacted with OKM-1, a monoclonal antibody directed against the human complement receptor type 3 (CR3, CD11b). This protein, p42, was designated p42-CR3. The antiserum against p42-CR3 was used for further purification of lysates by affinity chromatography. Three proteins of 66, 55, and 42 kDa were isolated. All were recognized by OKM-1 in immunoblots (p66-, p55-, and p42-CR3). The different proteins were separated and treated with neuraminidase and endoglycosidase F. Almost complete deglycosylation of the p66-CR3 protein was obtained after treatment with neuraminidase, indicating a high degree of glycosylation. Neuraminidase also had an effect on p55-CR3, but not on p42-CR3. Endoglycosidase F did not alter any of the three proteins. In ligand blots, p42-CR3 bound C3(H2O), C3b, and iC3b but not C3d; p55-CR3 clearly reacted with C3(H2O) and weakly reacted with C3b and iC3b. p66-CR3 never showed reactivity. It is suggested that p55 and p66 represent glycosylated forms of p42-CR3. Although C. albicans CR3 and human CR3 cross-react and bind identical ligands, the two receptors differ in structure.